Relations et solidarités entre les cités grecques de la côte sud de la mer Noire (viie-iiie s. av. J.-C.) - Claire Barat (Pallas, 2012)
For Antiquity, the Black Sea is looked upon as a Milesian or even Megaro-Milesian lake owing to the many settlements that sprang into life during the archaic era. The southern coast of the Black Sea appears as “the poor relation” of archeological research in comparison with the Bulgarian, Romanian, Ukrainian and Russian coasts the exploration of which during the xx. century made possible the study of the cities and their territories, of the relations of the Greeks with the native populations. The Turkish coast of the Black Sea being highly strategic during the Cold War and the Turkish towns occupying the sites of antique cities, the Turkish and international archeological missions had difficulties in undertaking excavations and bringing to light monuments or fossilized antique cadastral surveys.A good many sources (literary, epigraphic and numismatic) make it however possible to write a history of the relations of the Greek cities of the south coast of the Black Sea from the vii c. to the iii c. B.C., and evidence the importance of two cities, Heraclea of the Pontus and Sinope.In this article it will therefore be possible to see how the Greek cities of the south coast of the Black Sea react to inroads and assaults from outside (Athenian empire in the middle of the v c., passage of Xenophon and the remainder of the Ten-Thousand in 401-400, revolt of the satrap Damatès in 370, the unsettled condition of northern Anatolia within the Persian Empire in the middle of the iv c., Macedonian invasion of Anatolia and territorial ambitions of the Diadoques, establishment of the Bosphoran kingdom). We shall show how solidarities can emerge between Greek cities of the Black Sea’s southern coast (Sinope’s “colonial” system ?, alliance decree between Sinope and Heraclea in the middle of the iv. c, I. K-64 Sinope, n° 1) and how these cities had occasionally to appeal to other powers in hellenistic times (Heraclea and the North League, Sinope and Rhodes).